The Effect of Cow Manure on the Growth and Production of Lettuce (Lactuca sativa L.) - Wattimena, Anna Yuliana; Makaruku, Marlita Herlin; Amba, Martha (Agrikan Jurnal Agribisnis Perikanan, 2023)
Fertilizer is the main source of nutrients for plants in relation to growth, development and production processes every day. Manure is a waste product from pets that can be used to improve soil fertility, soil biology and soil physical properties. This study aims to determine the effect of cow manure on the growth and production of lettuce plants (Lactuca sativa L.). The experimental design used was a single-factor complete randomized design (RAL), namely the dose of cow manure. There are 5 types of cow manure treatments, namely S0 (control), S1 (600 grams / polybag), S2 (700 grams / polybag), S3 (800 grams / polybag), S4 (900 grams / polybag). The analysis used is variety analysis (anova) based on observed variables. If there is a real effect, it is followed by the smallest real difference test (BNT) level of 5%. The results of variety analysis and average difference tests show that the use of cow manure with various treatments has a very real effect on plant height, leaf area, header weight, root weight and has a real influence on the number of leaves. The dose of cow manure 600 grams / polybag can increase plant height growth, leaf area and fresh weight of plants.